Prevalence of traumatic dental injuries in primary teeth: A retrospective study - Gali Nagarjuna Chowdary; Ramkumar Hemalatha; Rajendran Vijayakumar; Rajendran Ganesh; Haridoss Selvakumar; Subramanian Mangaiyarkarasi (Wolters Kluwer Medknow Publications, 2014)
Introduction: Trauma to the oral region occurs frequently and comprises 5% of all injuries, which is more prevalent among preschoolers. Aim: The purpose of this retrospective study was to determine the prevalence of traumatic injuries to primary teeth reported to Department of Pedodontics and Preventive Dentistry, SRM Dental College, Chennai, during the years 2003-2013. Materials and Methods: The data was retrieved from records of patients according to sex, age, cause, number of injured teeth and type of tooth. A total number of 65,870 children reported, out of which 34,942 were boys and 30,928 were girls below the age of 6 years. All recorded data was analyzed with the SPSS software (15.0 version).The statistical analysis of the sample was performed using the Chi-square test. Results: The gender difference in the prevalence of traumatic dental injuries was statistically significant (males 66% vs. females 34% of which the maxillary central incisors are most affected (77.21%). Conclusion: Education to parents and caregivers regarding the epidemiology of traumatic injuries and emphasis on an early dental visit may play a major role in reducing the prevalence of dental injury and minimize their detrimental effects on children's quality of life.